(untitled) (Experimental biology, 2020)
The article presents the results of microbiological studies of phosphorus-containing wastes. 70 isolates were isolated, of which 36 isolates were assigned to bacteria, which corresponds to 51% of the total number of isolated microorganisms, 7 isolates were assigned to actinomycetes (10%) and 3 cultures to yeast (4%), 24 isolates were assigned to micromycetes (35%). Based on the screening of microorganisms, 14 of the most active strains that are promising for biogeotechnological purposes were selected. Based on the results of the study of cultural characteristics and PCR analysis data, the isolated strains were assigned to such types of micromycetes as: Aspergillus niger AsIA, Aspergillus tubingensis AsPN, Aspergillus terreus JOM, Aspergillus flavus AsZ, Aspergillus flavus AsF, to denitrifying bacteria Pseudomonas stutzeri NJA, to thermophilic bacteria Methyloversatilis thermotolerans MSO, Nitrosomonas europeae Nit1, Ralstonia pickettii ASA and Ralstonia pickettii TS, Acinetobacter sp. NAO, Alicyclobacillus tolerans ST (Sulfobacillus thermosulfidooxidans), Zoogloea resiniphila NS1, Gallionella capsiferriformans TS2, to acidophilic bacteria strains: Acidithiobacillus ferrooxidans ThIO, Acidithiobacillus thiooxidans ThIO . Key words: phosphorus waste, Acidithiobacillus ferrooxidans, Aspergillus niger, Nitrosomonas europeae, Gallionella capsiferriformans, Sulfobacillus thermosulfidooxidans.